An Imaging Measurement Study of Normal Knee Parameters in Southeast China - Liu, Huitong; Xu, Bingqiang; Feng, Eryou; Liu, Shizhang; Zhang, Wei; Qiu, Yusheng; Zhang, Yiyuan (Current Medical Imaging, 2022)
Background: Imaging measurement of distal femur and proximal tibia has been the hot point in the research of total knee arthroplasty and prosthesis development, which is an important treatment for patients with advanced knee joint disease. This study retrospectively investigated the digital imaging measurement of normal knee parameters in southeast China and evaluated their clinical value. Methods: From February 2010 to May 2014, and in accordance with the inclusion criteria, a total of 677 knees (334 female knees and 343 male knees) were categorized into 3 age groups. Clinical and digital imaging data, including the distal Femoral Condyle Diameter (FCD), Tibial Plateau Diameter (TPD), the distance between the medial tibial plateau and fibular head (DPF), tibiofemoral valgus angle, distal femoral valgus angle, Proximal Tibia (PT) varus angle and the angle from femoral condyle to tibial perpendicular (FT), were measured by using AutoCAD 10.0 software. All measured variables were statistically analyzed by SPSS statistical software (version 18.0). Results: Data are presented as the mean ± standard deviation. The normal female and male femoral condyle diameter was (7.69 ± 0.46) cm and (8.68 ± 0.55) cm, while the normal female and male tibial plateau diameter was (7.66 ± 0.46) cm and (8.60 ± 0.55) cm, respectively. The normal female and male DPF was (0.76 ± 0.36) cm and (0.79 ± 0.36) cm. For females and males, the tibiofemoral valgus angle and distal femoral valgus angle were (3.89 ± 2.20) ° and (3.29 ± 2.12) °, (9.03 ± 2.18) ° and (8.25 ± 2.20) °. As the two methods to measure tibial plateau varus angle, PT angle of normal female and male was (4.29 ± 1.86) ° and (4.84 ± 2.23) °, while the normal female and male FT angle was (5.34 ± 1.95) ° and (5.52 ± 2.07) °. Based on the data obtained, we found significant differences between the two genders in terms of the femoral condyle diameter and tibial plateau diameter in all age groups (P < 0.01). The DPF parameter showed an obvious difference between the young group and the middle-aged group (P < 0.05), and no significant difference was observed between the sides and genders (P > 0.05). The distal femoral valgus angle showed statistical differences between genders in the left side of the young group and middle-aged group (P < 0.05), while angle PT and FT showed no significant difference (P > 0.05). Conclusion: A large number of knee measurements was obtained, and a local knee database was developed in this study. Imaging measurement prior to total knee arthroplasty is clinically important for increasing the accuracy and long-term efficacy of total knee arthroplasty. These data can also provide useful information for knee surgery and sports medicine as well as prosthesis development.
Keywords: digital imaging measurement